2017
DOI: 10.1001/jamaneurol.2017.0934
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Involvement in Antisynthetase Syndrome

Abstract: IMPORTANCE Antisynthetase syndrome, characterized by myositis, interstitial lung disease, skin rash, arthropathy, and Raynaud phenomenon, is a clinical entity based on the presence of aminoacyl transfer RNA synthetase (ARS) antibodies in patients' serum. However, antisynthetase syndrome is not included in the histological subsets of idiopathic inflammatory myopathies.OBJECTIVE To elucidate the clinical features of myositis in patients with antisynthetase syndrome. DESIGN, SETTING, AND PARTICIPANTSIn this cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 32 publications
(83 reference statements)
5
92
0
6
Order By: Relevance
“…ASS is associated with anti‐aminoacyl transfer RNA synthetase autoantibodies and clinically with myositis, characteristic skin lesion (mechanic's hands are typical, but heliotrope rash and Gottron's signs/papules can also be seen), Raynaud phenomenon, interstitial lung disease, arthritis/arthralgia, and systemic symptom such as fever . Some of the clinical features and a pathological finding of perifascicular reinforcement of human leucocyte antigen (HLA)‐ABC [major histocompatibility complex (MHC) class I] expression on the sarcoplasm are shared with DM, yet ASS has a unique myopathological phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASS is associated with anti‐aminoacyl transfer RNA synthetase autoantibodies and clinically with myositis, characteristic skin lesion (mechanic's hands are typical, but heliotrope rash and Gottron's signs/papules can also be seen), Raynaud phenomenon, interstitial lung disease, arthritis/arthralgia, and systemic symptom such as fever . Some of the clinical features and a pathological finding of perifascicular reinforcement of human leucocyte antigen (HLA)‐ABC [major histocompatibility complex (MHC) class I] expression on the sarcoplasm are shared with DM, yet ASS has a unique myopathological phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…We selected 30 patients with ASS [65 (13–85) years of age at biopsy: median and range, sex ratio (male:female) 1:1.7], 9 with IMNM [four positive for anti‐signal recognition particle (SRP) and five positive for anti‐3‐hydroxy‐3‐methylglutaryl‐CoA reductase (HMGCR) autoantibodies] [39 (10–61) years of age, 1:0.8], 5 with IBM [63 (57–69) years of age, 1:0.7] and 7 with muscular dystrophy (three with dystrophinopathy and four with dysferlinopathy) [39 (6–80) years of age, 1:0.4]. The autoantibodies in their sera were measured by means of RNA and protein immunoprecipitation for anti‐aminoacyl transfer RNA synthetase antibodies (anti‐OJ, ‐EJ and ‐KS), addressable laser bead immunoassay for anti‐TIF1‐γ, ‐SRP and ‐HMGCR antibodies or line‐immunoassay (D‐Tek, Mons, Belgium) for the others as previously described . We chose subjects in a consecutive manner within each disease group and investigated their frozen skeletal muscle samples that were first biopsied.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the rather high incidence of fasciitis in patients with ASS may account for the different inflammatory processes in the subtypes of dermatomyositis: type 1 interferon‐mediated myositis, and perifascicular necrosis rather characteristic for ASS . It has been reported that patients with myopathy with “perimysial pathology” showed a selective increase of ALD, and the clinical symptoms of such patients are similar to ASS .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inflammatory infiltrates (e.g., CD8+ cells and a lesser number of macrophages) surround and invade non‐necrotic muscle fibers expressing major histocompatibility complex class I antigens within the fascicles in patients with PM . In their study of antisynthetase syndrome, Noguchi et al observed that mononuclear cells infiltrated into perimysial sites (usually perivascular sites) but did not surround the endomysium or invade into non‐necrotic muscle fibers within the fascicles, as is typically observed in PM. Basically, the sites of inflammatory infiltrates in antisynthetase syndrome are similar to those in DM, but not in PM.…”
mentioning
confidence: 96%